Barriers towards employees' structural and psychological empowerment: A study of non-managerial employees in governmental service organizations in Cairo - Bassem, Passant (AUC Knowledge Fountain, 2015)
The aim of this thesis is to pave the way for non-managerial employees’ empowerment in governmental service organizations in Egypt. Based on a review of previous studies that discussed the Egyptian bureaucracy, this study hypothesized that all the structural and psychological empowerment barriers - namely the organizational cultures and work context factors, managerial employees’ leadership style, and non-managerial employees’ readiness level and personalities - do exist within the governmental service organizations. Questionnaires were distributed to 223 non-managerial employees in Real Estate offices, Social Insurance and Pension offices, Traffic Services offices, Civil Registry offices, Health offices (Ministry of Health), Tax offices, and Courts’ Registry and Record offices all over Cairo. Statistical analyses of the findings of 183 eligible questionnaires reveal that ‘non-managerial employees’ inability to be empowered’ is the only empowerment barrier that does exist within governmental service organizations. Results have been inconclusive for the organizational cultures. The thesis concludes by providing recommendations for facilitating non-managerial employees’ empowerment, and offering suggestions for future research based on the limitations identified in this study.